2023
DOI: 10.1111/jcmm.17841
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin suppresses gastric cancer SGC‐7901 cell proliferation by targeting the TNF‐alpha/androgen receptor/TGF‐beta signalling pathway axis

Abstract: Statistics provided by GLOBOCAN list gastric cancer as the sixth most common, with a mortality ranking of third highest for the year 2020. In China, a herb called Rabdosia rubescens (Hemsl.) H.Hara, has been used by local residents for the treatment of digestive tract cancer for hundreds of years. Oridonin, the main ingredient of the herb, has a curative effect for gastric cancer, but the mechanism has not been previously clarified. This study mainly aimed to investigate the role of TNF‐alpha/Androgen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…This process is mainly depended on extracellular matrix metalloproteinases (MMPs). 34 , 35 Overexpressed MMPs often degrade basement membrane and ECM, then promote tumor angiogenesis and invasion. 36 , 37 MMP24 is a subfamily of matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…This process is mainly depended on extracellular matrix metalloproteinases (MMPs). 34 , 35 Overexpressed MMPs often degrade basement membrane and ECM, then promote tumor angiogenesis and invasion. 36 , 37 MMP24 is a subfamily of matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…ORI may help inhibit the proliferation and fibrogenesis of hepatic stellate cells as it stimulates cell cycle arrest and cancerous cell apoptosis through p53-p21 pathways and does not cause toxicity in hepatocytes (Bohanon et al, 2014). genes can also be used as prognostic biomarkers (Gao et al, 2021;Gao et al, 2023).…”
Section: Liver Cancermentioning
confidence: 99%
“…The liver cancer survival rate was linked to ESR1, SPP1, and FOSB gene expression. Study reported that AURKA, SPP1, NUSAP1, UBE2C, TOP2A, AFP, PTTG1, GMNN, RRM2, CXCL12, SPARCL1, FOS, SOCS3, DCN, PCK1, and FOSB can be used as diagnostic biomarkers for liver cancer, among which FOBS and SPP1 genes can also be used as prognostic biomarkers (Gao et al., 2021 ; Gao et al., 2023 ).…”
Section: Ori Activity In Different Cancers In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no breakthrough in the overall treatment of brain glioma, and the search for effective treatment methods is still a hot spot in clinical research. Traditional Chinese medicine (TCM) has a long history, and more and more studies on the treatment of malignant tumors with Chinese medicine are being conducted, which has gained wide attention [ 3 , 4 ]. The complex composition of Chinese medicine, especially the TCM formula, could exert anti-tumor effects from multiple targets and has great potential and advantages in the treatment of malignant tumors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%